Recent Developments and Applications in The Vehicular Embedded System Technologies - Bhaskar Roy (AG Volumes, 2022)
In the last two decades, the no. of the computer-based features incorporated in automobiles has increased significantly. Even though vehicle manufacturing is expected to rise modestly in the next years, the embedded electronics, and specifically embedded software, is rising. In addition, hardware components' quality and performance are improving whereas their price is declining. Many novel functionalities that would be prohibitively expensive or impossible to implement using the mechanical as well as hydraulic technology may now be implemented using the software technology, thus addressing the end user's needs in the terms of safety as well as comfort. Customers can now purchase a secure, effective, and customised vehicle owing to such technologies, whereas carmakers seem to be able to the master product differentiation as well as the innovation. Several studies have indeed been undertaken to improve embedded system design and the newest technologies to create smart automobiles, which are reviewed in this article. DSPs, ASICs, FPGAs, as well as other microprocessor-based embedded systems are only a few of the many options out now (field-programmable gate arrays). There has been a lot of recent discussion on the use of AI (artificial intelligence) as well as fuzzy logic controllers in automobiles.